Impact of Endometriosis in Women of Arab Ancestry on: Health-Related Quality of Life, Work Productivity, and Diagnostic Delay - Mousa, Mira; Al-Jefout, Moamar; Alsafar, Habiba; Becker, Christian M.; Zondervan, Krina T.; Rahmioglu, Nilufer (Frontiers in Global Women's Health, 2021)
Introduction Endometriosis has a negative effect on health-related quality of life (HRQoL), wellbeing and daily functioning. Endometriosis is an under-researched condition within non-western populations. Cultural representations are needed to understand the relative roles of societal norms, traditional factors, and religious sensitivities on the impact of endometriosis on HRQoL in various populations. In particular, there is a lack of emphasis placed in understanding the association of HRQoL on endometriosis in Arab women. Method In this prospective case-control study, 2,610 Arab ancestry women in the United Arab Emirates were recruited to investigate the impact of endometriosis on HRQoL, diagnostic delay, psychological co-morbidities, work productivity, and physical activity. Participants completed the following standardized, validated questionnaires: Short Form-36 version 2 questionnaire, the World Endometriosis Research Foundation EPHect minimum clinical questionnaire version, and Work Productivity and Activity Impairment questionnaire. Translations to the Arabic language, validated using the forward-backward translation method, of the questionnaires were utilized. Results HRQoL scores were significantly impaired in women with endometriosis, as demonstrated in the Physical Composite Scores and Mental Composite Scores in the symptomatic control group (p=0.001; p=0.003, respectively) and the asymptomatic control group (p<0.001; p<0.001, respectively). Susceptibility and severity of multiple pain syndromes and infertility in women with endometriosis was the main indicator of lower HRQoL. Anxiety (p=0.007) and depression (p=0.005) were significantly associated with endometriosis, in comparison to symptomatic controls. The average diagnostic delay was 11.61 years, however single women experience 15.81 years of diagnosis delay, with approximately 18% (n=15) of the single women experiencing more than a 20-year delay in diagnosis. The intensity of physical activity was not associated with endometriosis, when compared to symptomatic (p=0.405) or asymptomatic controls (p=0.144). Conclusion For the first time, we provide evidence from a combined hospital, clinic, and population-based study that Arab women with endometriosis experience significant impacts on HRQoL, substantial diagnostic delay after the onset of symptoms, significant association to psychological disorders (anxiety and depression), and a negative impact on work productivity. Future research must focus on understanding the personal and culturally centered beliefs of Arab women to ensure a positive HRQoL trajectory by improving diagnosis and management strategies.